Prenatal control of severe thalassaemia: Chiang Mai strategy - Tongsong T. (2014)
Prenatal diagnosis of severe thalassaemia is conventionally diagnosed by fetal DNA analysis but it can not be widely used due to its drawbacks of high cost and technical effort. This prospective study describes a new prenatal strategy in preventing severe thalassaemia by a more simple and inexpensive way. The strategy included: (1) genetic counselling; (2) identification of pregnancies at risk by retrospective screening (history of known risk) and prospective screening for asymptomatic women; (3) cordocentesis at 16-22 weeks' gestation; (4) fetal blood analysis with high performance liquid chromatography (HPLC); (5) termination of affected pregnancy. The prospective screening consisted of 2 min osmotic fragility (OF) and HbE screening test in women with no risk, and testing the husbands of the women with a positive result. If both of the couple had a positive result, the diagnostic test (HbA(2) level and PCR alpha-thal 1) for the carrier was needed. A pregnancy in which both of the couple were carriers was considered at risk. This strategy identified 181 and 108 couples at risk by prospective (from 7954 pregnancies) and retrospective screening, respectively. Two hundred and forty-two underwent cordocentesis, 108 from retrospective screening and 134 from prospective screening, and 62 were proven to have severe thalassaemia (29 and 33 in retrospective and prospective screening, respectively). The strategy identified nearly all, if not all, fetuses with severe thalassaemia without false positives among the screened couples. In conclusion, the strategy proves to be highly effective in the control of severe thalassaemia.